2017
DOI: 10.3906/sag-1511-66
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning in pediatric patients with pectus excavatum and pectus carinatum

Abstract: Background/aim: Pectus excavatum and pectus carinatum are the most commonly seen anterior chest wall deformities. Recent studies reveal that minimal invasive repair of pectus deformities improves the quality of life. Our aim is to assess the psychosocial functioning and sociodemographic characteristics of pediatric patients with pectus deformities and evaluate the differences between patients operated on with minimal invasive repair techniques and nonoperated patients.Materials and methods: Thirty-two patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…Two studies found no statistically significant results after therapy. 15,17 In conclusion, the literature reveals a great concern for psychosocial issues in CWD patients. Most articles describe improvement in QoL after surgery.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Two studies found no statistically significant results after therapy. 15,17 In conclusion, the literature reveals a great concern for psychosocial issues in CWD patients. Most articles describe improvement in QoL after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…However, another study published later in 2017 found no statistically significant differences between operated and non-operated patient groups in terms of total scores on the psychiatric rating scales. 15…”
Section: Articles Relating To Both Pectus Excavatum and Pectus Carinatummentioning
confidence: 99%
See 1 more Smart Citation
“…Các nghiên cứu khác ở Việt Nam và thế giới cũng cho thấy bệnh lõm ngực gây ra các triệu chứng lâm sàng tương tự [7]. Triệu chứng thiếu sức khi tập luyện có ở 58,8% trường hợp trong nghiên cứu của tác giả Lâm Văn Nút (2014) [6], 67% trong nghiên cứu của tác giả Fonkalsrud (2000) [5] và 82% trong nghiên cứu của tác giả Nuss (2008) [8].…”
Section: Biểu đồ 2: Phân Tích Triệu Chứng Lâm Sàng Theo độ Tuổiunclassified
“…В зарубежных исследованиях, посвященных психологическому состоянию подростков с указан-ным заболеванием [10][11][12], использовались преиму-щественно опросники, оценивающие те или иные признаки в баллах, которые обеспечили обширную базу знаний по данной проблеме. В настоящем ис-следовании мы стремились качественно оценить показатели, отражающие степень психологическо-го благополучия подростков с ВДГК, самооценку и тревожность.…”
unclassified